Silica scale inhibitor
A (meth)acrylic acid-based copolymer with a specific composition effectively inhibits silica scale, addressing the inadequacies of existing water treatment agents and enhancing silica scale prevention in diverse applications.
Patent Information
- Application Number
- JP2021011332
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-01-27
AI Technical Summary
Existing water treatment agents are inadequate in effectively inhibiting silica scale, and there is a need for polymers made from readily available general-purpose monomers suitable for various water treatment applications.
A (meth)acrylic acid-based copolymer containing a structural unit derived from sulfonic acid (salt) group-containing monomer, with a specific monomer content and weight average molecular weight, is developed to enhance silica scale inhibition.
The copolymer exhibits excellent ability to suppress silica scale, making it suitable as a silica scale inhibitor for various water treatment processes.
Smart Images

Figure 0007607463000001 
Figure 0007607463000002 
Figure 0007607463000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a silica scale inhibitor, and more particularly to a silica scale inhibitor used to inhibit silica scale generation in various water treatment processes. [Background technology]
[0002] For example, in geothermal power generation, industrial cooling water, and seawater desalination, the generation of scale such as calcium carbonate and silica can be a problem. For example, Patent Document 1 discloses that a copolymer containing 16 mol % or more and 24 mol % or less of structural units derived from a sulfonic acid group-containing monomer and 76 mol % or more and 84 mol % or less of structural units derived from (meth)acrylic acid (salt), having a sulfonic acid (salt) group at at least one main chain end and having a weight average molecular weight of 1,000 to 18,000, has excellent gel resistance and high calcium ion chelating ability, and therefore can be suitably used as a water treatment agent such as a scale inhibitor. For example, Patent Document 2 discloses that the copolymer described in the invention improves the dispersibility of hydrophobic particles and also exhibits excellent chelating ability for calcium ions, thereby enabling it to exhibit extremely good scale prevention ability for the piping and inside of geothermal power generation equipment, and therefore can be suitably used as a scale inhibitor for geothermal power generation equipment. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2013 / 147171 [Patent Document 2] JP 2016-064382 A Summary of the Invention [Problem to be solved by the invention]
[0004] As described above, water treatment agents such as scale inhibitors have been proposed, but there is a demand for further improvement in the silica scale inhibition ability, and there has been a need for a silica scale inhibitor that is produced from a polymer using a readily available general-purpose monomer and that can be applied to prevent silica scale in a variety of water treatment applications. An object of the present invention is to provide a (meth)acrylic acid-based copolymer that has excellent silica scale inhibition ability and can therefore be suitably used, for example, as a silica scale inhibitor. [Means for solving the problem]
[0005] The present inventors have conducted various investigations to achieve the above object and have arrived at the present invention. In other words, the scale inhibitor of the present disclosure is a copolymer containing structural units derived from (meth)acrylic acid (salt) and structural units derived from a monomer containing a sulfonic acid (salt) group, and is characterized in that the structural units derived from the monomer containing a sulfonic acid (salt) group account for 11 mol % or more of the structures derived from all monomers (100 mol %), and the weight average molecular weight is 9,200 or less. Effect of the Invention
[0006] The silica scale inhibitor containing the (meth)acrylic acid-based copolymer of the present disclosure exhibits good silica scale inhibition ability and can therefore be preferably used as a silica scale inhibitor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention will be described in detail below. In addition, a combination of two or more of the individual preferred embodiments of the present invention described below is also a preferred embodiment of the present invention.
[0008] [Copolymer of the present disclosure] The copolymer of the present disclosure is a copolymer containing structural units derived from (meth)acrylic acid (salt) and structural units derived from a monomer containing a sulfonic acid (salt) group, and is a (meth)acrylic acid-based copolymer characterized in that the structural units derived from the monomer containing a sulfonic acid (salt) group are 11 mol % or more relative to 100 mol % of structures derived from all monomers, and the weight average molecular weight is 9200 or less. The above copolymer may be referred to as the copolymer of the present disclosure.
[0009] <Structural unit derived from (meth)acrylic acid (salt)> In this disclosure, (meth)acrylic acid refers to acrylic acid, methacrylic acid, and salts thereof. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, a structural unit derived from (meth)acrylic acid (salt) refers to a structural unit in which a carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond. For example, acrylic acid, CH 2 =CH(COOH), the structural unit derived from acrylic acid is -CH 2 It can be represented by -CH(COOH)-. The structural unit derived from (meth)acrylic acid (salt) can be formed, for example, by radical polymerization of (meth)acrylic acid (salt). The structural unit derived from (meth)acrylic acid (salt) may have the same structure as the structure in which the carbon-carbon double bond of (meth)acrylic acid (salt) is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of (meth)acrylic acid (salt), and may be, for example, a structural unit formed by a post-reaction after polymerization.
[0010] The content of the structural unit derived from (meth)acrylic acid (salt) in the copolymer of the present disclosure is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more, based on 100 mol% of the structural units derived from all monomers constituting the copolymer of the present disclosure. It is also preferably 89 mol% or less, more preferably 86 mol% or less. The content of the structural unit derived from the (meth)acrylic acid (salt) is calculated in terms of (meth)acrylic acid. The term "in terms of (meth)acrylic acid" means that even if the structural unit derived from (meth)acrylic acid (salt) is a structural unit derived from a (meth)acrylic acid salt, the mass is calculated as (meth)acrylic acid. By being in the above range, the silica scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved.
[0011] <Structural unit derived from monomer containing sulfonic acid (salt) group> In the present disclosure, a sulfonic acid (salt) group-containing monomer refers to a compound that contains at least one carbon-carbon double bond and a sulfonic acid (salt) group. The at least one carbon-carbon double bond is usually radically polymerizable. The above salt is not particularly limited, but examples thereof include alkali metal salts, alkaline earth metal salts, transition metal salts, and ammonium salts. In the present disclosure, the structural unit derived from a sulfonic acid (salt) group-containing monomer refers to a structural unit in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from a sulfonic acid (salt) group-containing monomer may have the same structure as the structure in which at least one carbon-carbon double bond of a sulfonic acid (salt) group-containing monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of a sulfonic acid (salt) group-containing monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. Examples of sulfonic acid (salt) group-containing monomers include vinyl sulfonic acid and its salts, styrene sulfonic acid and its salts, (meth)allyl sulfonic acid and its salts, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid and its salts, 3-(meth)allyloxy-1-hydroxypropanesulfonic acid and its salts, 2-(meth)allyloxyethylenesulfonic acid and its salts, and 2-acrylamido-2-methylpropanesulfonic acid and its salts.
[0012] For example, a structural unit derived from a sulfonic acid (salt) group-containing monomer is represented by the following general formula (1). TIFF0007607463000001.tif37114 (in general formula (1), R 1 represents a hydrogen atom or a methyl group, and X and Y each independently represent a hydroxyl group or a sulfonic acid (salt) group (provided that at least one of X and Y represents a sulfonic acid (salt) group. Sulfonic acid (salt) refers to sulfonic acid and sulfonate salts. The salts of sulfonate salts include metal salts, ammonium salts, and organic amine salts. Specific examples of such salts include alkali metal salts such as sodium salt, lithium salt, and potassium salt; alkaline earth metal salts such as magnesium salt and calcium salt; transition metal salts such as iron salt; and alkanoic acid salts such as monoethanolamine salt, diethanolamine salt, and triethanolamine salt. Examples of the structural unit containing the atom represented by the asterisk include, but are not limited to, a structural unit derived from a monomer, a structural unit derived from an initiator, a structural unit derived from a chain transfer agent, and the like. Since the scale inhibitor of the present disclosure has a tendency to have improved scale inhibition ability, 3-(meth)allyloxy-2-hydroxypropanesulfonic acid and its salts are preferred, and 3-allyloxy-2-hydroxypropanesulfonic acid and its sodium salt are more preferred.
[0013] The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer in the copolymer of the present disclosure is 11 mol% or more, more preferably 12 mol% or more, and even more preferably 13 mol% or more, based on 100 mass% of the structural units derived from all monomers constituting the copolymer of the present disclosure. Also, it is preferably 40 mol% or less, more preferably 30 mol% or less, and even more preferably 25 mol% or less. The content of the structural unit derived from the sulfonic acid (salt) group-containing monomer is calculated in terms of sodium salt. The calculation in terms of sodium salt means that even if the sulfonic acid (salt) group contained in the structural unit derived from the sulfonic acid (salt) group-containing monomer is, for example, an acid type sulfonic acid group, it is calculated as the sodium salt of the sulfonic acid group. By being in the above range, the silica scale inhibition ability of the scale inhibitor of the present disclosure tends to be improved.
[0014] <Structural units derived from other monomers> The copolymer of the present disclosure may, if desired, have structural units derived from monomers other than (meth)acrylic acid (salt)-derived structural units and sulfonic acid (salt) group-containing monomers (also referred to as structural units derived from other monomers). In the present disclosure, the structural unit derived from another monomer refers to a structural unit in which at least one carbon-carbon double bond of another monomer is replaced with a carbon-carbon single bond. Note that the structural unit derived from another monomer may have the same structure as the structure in which at least one carbon-carbon double bond of the other monomer is replaced with a carbon-carbon single bond, and is not limited to a structural unit formed by polymerization of the other monomer, and may be, for example, a structural unit formed by a post-reaction after polymerization. The content of structural units derived from other monomers in the copolymer of the present disclosure is, relative to 100 mol% of structural units derived from all monomers constituting the copolymer of the present disclosure, 0 mol% or more and 15 mol% or less, preferably 0 mol% or more and 10 mol% or less, more preferably 0 mol% or more and 5 mol% or less, even more preferably 0 mol% or more and 3 mol% or less, particularly preferably 0 mol% or more and 2 mol% or less, and most preferably 0 mol%.
[0015] Examples of the other monomers include carboxyl group-containing monomers such as maleic acid, itaconic acid, and salts thereof; unsaturated alcohols such as (meth)allyl alcohol and isoprenol, and monomers obtained by adding alkylene oxides thereto; polyalkylene glycol chain-containing monomers such as (meth)acrylic acid esters of alkoxyalkylene glycols; vinyl aromatic monomers having heterocyclic aromatic hydrocarbon groups such as vinylpyridine and vinylimidazole; dialkylaminoalkyl (meth)acrylates such as dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, and dimethylaminopropyl acrylate; dialkylaminoalkyl (meth)acrylamides such as dimethylaminoethyl acrylamide, dimethylaminoethyl methacrylamide, and dimethylaminopropyl acrylamide; allylamines such as diallyl alkylamines such as diallyl amine and diallyl dimethylamine; and quaternized products thereof; N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, N-vinyl-N-methylformamide, N-vinyl-N-methyl N-vinyl monomers such as acetamide and N-vinyl oxazolidone; amide monomers such as (meth)acrylamide, N,N-dimethylacrylamide, N-isopropylacrylamide, and t-butylacrylamide; hydroxyl group-containing monomers such as (meth)allyl alcohol and isoprenol; (meth)acrylic acid alkyl ester monomers such as butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and dodecyl (meth)acrylate; 2-hydroxyethyl (meth)acrylate, and 2-hydroxypropyl (meth)acrylate. (meth)acrylate hydroxyalkyl monomers such as 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyhexyl (meth)acrylate; vinyl aryl monomers such as styrene, indene, and vinyl aniline; isobutylene, vinyl acetate, and the like; ether bond-containing monomers include vinyl ethers such as ethyl vinyl ether, butyl vinyl ether, and benzyl vinyl ether; (meth)allyl ethers such as ethyl methallyl ether, butyl methallyl ether, and benzyl methallyl ether;Examples of isoprenyl ethers include ethyl isoprenyl ether, butyl isoprenyl ether, and benzyl isoprenyl ether.
[0016] <Other structural units> The copolymer of the present disclosure may have a sulfonic acid (salt) group at at least one end of the polymer main chain. Having a sulfonic acid (salt) group at at least one end of the polymer main chain means having a sulfonic acid (salt) group at one or more ends of the main chain. For example, in the case of a linear polymer, there are two main chain ends, and one or both of them may have a sulfonic acid group, and for example, in the case of a polymer having a branched structure, there are three or more main chain ends, and one or more of them may have a sulfonic acid group. When having a sulfonic acid (salt) group at at least one chain end, the mass% of the sulfonic acid group at the main chain end of the copolymer relative to 100% by mass of the copolymer is preferably 0.01% or more and 10% or less, and more preferably 0.01% or more and 5% or less. The conversion of the sulfonic acid group is calculated based on the acid group.
[0017] <Physical properties of the copolymer of the present disclosure> The copolymer of the present disclosure has a weight average molecular weight (Mw) of not more than 9200. In addition, the weight average molecular weight is preferably not less than 1000. By being in the above range, the silica scale inhibiting ability of the scale inhibitor of the present disclosure tends to be further improved. The copolymer of the present disclosure contains acid groups such as carboxylic acid (salt) groups and sulfonic acid (salt) groups, but the acid groups of the copolymer of the present disclosure may be neutralized. The total neutralization rate of the acid groups is preferably 1 mol% or more and 90 mol% or less. The neutralization rate can be calculated, for example, by ordinary acid-base titration.
[0018] <Method for producing the copolymer of the present disclosure> The method for producing the copolymer of the present disclosure is not particularly limited, but it is usually preferable to produce the copolymer by polymerizing structural units derived from (meth)acrylic acid (salt), a sulfonic acid (salt) group-containing monomer, and other monomers as necessary. In the process for producing the copolymer of the present disclosure, a polymerization initiator can be used in the polymerization of the monomer. In the process for producing the copolymer of the present disclosure, a chain transfer agent can be used as necessary to adjust the molecular weight.
[0019] <Chain transfer agent of the present disclosure> The chain transfer agent of the present disclosure can be used to adjust the molecular weight. For example, bisulfite (salt) such as bisulfite, metabisulfite, sodium bisulfite, potassium bisulfite, sodium metabisulfite, potassium metabisulfite, mercaptoethanol, thioglycerol, thioglycolic acid, 2-mercaptopropionic acid, 3-mercaptopropionic acid, thiomalic acid, octyl thioglycolate, octyl 3-mercaptopropionate, 2-mercaptoethanesulfonic acid, n-dodecyl mercaptan, octyl mercaptan, butyl thioglycolate, and other thiol-based chain transfer agents; halides such as carbon tetrachloride, methylene chloride, bromoform, and bromotrichloroethane; secondary alcohols such as isopropanol and glycerin; phosphorous acid, hypophosphorous acid, and salts thereof (sodium hypophosphite, potassium hypophosphite, and the like); and the like. Among these, in the production of the copolymer according to the present disclosure, bisulfites (salts) can be used to contain a sulfonic acid group at at least one main chain end. This allows efficient introduction of a sulfonic acid group at at least one main chain end of the copolymer obtained. One type of chain transfer agent may be used, or two or more types may be used. The amount of chain transfer agent added is not limited as long as the monomers can be polymerized well, but is preferably 0.001 mol or more and 0.1 mol or less, more preferably 0.001 mol or more and 0.08 mol or less, relative to 1 mol of the monomer mixture to be copolymerized.
[0020] <Polymerization initiator of the present disclosure> In the process of producing the copolymer of the present disclosure, a polymerization initiator is usually used. Known polymerization initiators can be used. For example, persulfates such as sodium persulfate, potassium persulfate, and ammonium persulfate, hydrogen peroxide, dimethyl 2,2-'azobis(2-methylpropionate), 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyric acid) dimethyl, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropionate), azo compounds such as 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] dihydrochloride, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n hydrate, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] disulfate dihydrate, and 1,1'-azobis(cyclohexane-1-carbonitrile); and organic peroxides such as benzoyl peroxide, lauroyl peroxide, peracetic acid, di-t-butyl peroxide, and cumene hydroperoxide. Among these, persulfates are preferred.
[0021] [Uses of the Copolymer of the Present Disclosure] The copolymer of the present disclosure can exhibit high performance in aqueous applications and can be preferably used as a scale inhibitor for use in geothermal power generation processes, oil well and gas well processes, seawater desalination processes or waste liquid concentration processes using forward osmosis membranes or reverse osmosis membranes, boiler water circulation systems, cooling water circulation systems, and the like. The copolymer of the present disclosure can be preferably used as an inhibitor of, for example, silica scale or calcium carbonate scale, and is most preferably used as an inhibitor of silica scale because of its excellent silica scale inhibition ability.
[0022] [Silica scale inhibitor of the present disclosure] The silica scale inhibitor of the present disclosure contains the copolymer of the present disclosure. The silica scale inhibitor of the present disclosure preferably contains the copolymer of the present disclosure at 1 mass% or more and 100 mass% or less. More preferably, the copolymer of the present disclosure is contained at 1 mass% or more and 80 mass% or less, and even more preferably, the copolymer of the present disclosure is contained at 1 mass% or more and 50 mass% or less. The silica scale inhibitor of the present disclosure may contain components other than the copolymer of the present disclosure. Examples of components other than the copolymer of the present disclosure include solvents such as water, pH adjusters such as alkalis and acids, oxygen scavengers, anticorrosive agents, chelating agents, phosphonic acids (salts) such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, and salts thereof, carboxyl group-containing polymers other than the copolymer of the present disclosure, surfactants, antifoaming agents, pitch control agents, slime control agents, and the like.
[0023] [Water treatment agent of the present disclosure] The water treatment agent of the present disclosure includes the scale inhibitor of the present disclosure. The water treatment agent of the present disclosure preferably contains, for example, 1% by mass or more and 70% by mass or less of the copolymer of the present disclosure. It is more preferable that the copolymer contains 1% by mass or more and 50% by mass or less, more preferably 1% by mass or more and 40% by mass or less, particularly preferably 1% by mass or more and 30% by mass or less, and most preferably 1% by mass or more and 20% by mass or less. The water treatment agent of the present disclosure may contain components other than the scale inhibitor of the present disclosure. Examples of components other than the scale inhibitor of the present disclosure include solvents such as water; pH adjusters such as alkalis and acids; oxygen scavengers; anticorrosive agents; chelating agents; phosphonic acids (salts) such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, and salts thereof; carboxyl group-containing polymers other than the copolymer of the present disclosure; surfactants; defoamers; pitch control agents; slime control agents, etc.
[0024] [Silica scale prevention method of the present disclosure] The silica scale prevention method of the present disclosure uses the silica scale inhibitor of the present disclosure or the copolymer of the present disclosure. The silica scale prevention method of the present disclosure preferably includes a step of adding the silica scale inhibitor of the present disclosure or the copolymer of the present disclosure to a system to be prevented from silica scale formation. Also, preferably, the method includes a step of controlling the amount of the copolymer of the present disclosure in the system to be prevented from silica scale formation so as to be within a predetermined range. The content of the copolymer of the present disclosure in the system to be prevented from silica scale formation is preferably 0.1 ppm or more and 500 ppm or less, more preferably 0.1 ppm or more and 300 ppm or less. EXAMPLES
[0025] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". <Weight average molecular weight measurement conditions (GPC)> Equipment: Tosoh Corporation HLC8320 Column: SHODEX Asahipak GF-310-HQ, Showa Denko Corporation; GF-710-HQ, GF-1G-7B Column temperature: 40℃ Flow rate: 0.5ml / min Calibration curve: Polyacrylic acid standard manufactured by American Polymer Standards Corporation Polyacrylic acid standard Eluent: 0.1N sodium acetate
[0026] <Synthesis Example (1)> 250.7g of pure water and 0.031g of Mohr's salt were charged into a 3L SUS reaction vessel equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 85°C while stirring to prepare a polymerization reaction system. Next, 484.9g of 80% acrylic acid aqueous solution (hereinafter also referred to as "80% AA"), 499.6g of 40% aqueous solution of sodium 3-allyloxy-2-hydroxypropanesulfonate (hereinafter also referred to as "40% HAPS"), 168.0g of 15% aqueous solution of sodium persulfate (hereinafter also referred to as "15% NaPS"), and 96.9g of 35% aqueous solution of sodium hydrogen sulfite (hereinafter also referred to as "35% SBS") were dropped from separate nozzles into the polymerization reaction system maintained at 85°C under stirring. The drop time of each solution was 180 minutes for 80% AA, 140 minutes for 40% HAPS, 200 minutes for 15% NaPS, and 170 minutes for 32.5% SBS. The drop speed of each solution was constant, and each solution was continuously dropped. After the drop of 15% NaPS was completed, the reaction solution was kept at 85°C (aged) for another 30 minutes to complete the polymerization. In this way, a polymer aqueous solution (1) with a solid content concentration of 43.8% was obtained. The weight average molecular weight of the polymer (1) was 8200. The composition ratio of the charged polymer was the same as that of the produced polymer.
[0027] <Synthesis Example (2)> 250.78g of pure water and 0.031g of Mohr's salt were charged into a 3L SUS reaction vessel equipped with a reflux condenser and a stirrer (paddle blade), and the temperature was raised to 85°C while stirring to prepare a polymerization reaction system. Next, 508.9g of 80% AA, 524.3g of 40% HAPS, 176.3g of 15% NaPS, and 39.7g of 10% SBS were dropped from separate nozzles into the polymerization reaction system maintained at 85°C under stirring. The drop times of each solution were 180 minutes for 80% AA, 140 minutes for 40% HAPS, 200 minutes for 15% NaPS, and 170 minutes for 10% SBS. The drop speed of each solution was constant, and each solution was dropped continuously. After the drop of 15% NaPS was completed, the reaction solution was maintained (aged) at 85°C for another 30 minutes to complete the polymerization. In this way, an aqueous polymer solution (2) with a solid content of 44.5% was obtained. The weight average molecular weight of the polymer (2) was 49000. The composition ratio of the charged polymer and the produced polymer was the same.
[0028] <Synthesis Example (3)> In a 2.5L SUS316 separable flask equipped with a thermometer, reflux condenser and stirrer, 258.3g of pure water and 0.033g of Mohr's salt were charged, and the temperature was raised to 85°C under stirring (initial charge). Next, 464.9g of 80% AA, 618.0g of 40% HAPS, 168.0g of 15% by mass NaPS, and 72g of 35% by mass SBS were dropped from separate dropping nozzles into the copolymerization reaction system at a constant temperature of 85°C under stirring. The dropping times for each were 180 minutes for 80% AA, 140 minutes for 40% HAPS, 170 minutes for 35% SBS, and 200 minutes for 15% NaPS. All of the droppings were started at the same time. After the dropping was completed, the reaction solution was kept at 85°C for another 60 minutes to mature and complete the copolymerization. In this way, an aqueous polymer solution (3) with a solid content of 46% was obtained. The weight average molecular weight of the polymer (3) was 10000. The composition ratio of the charged polymer and the produced polymer was the same.
[0029] <Polymerized Silica Scale Inhibition Rate Evaluation Test> Sodium silicate aqueous solution: Add ion-exchanged water to 2.129 g of sodium metasilicate nonahydrate (manufactured by Aldrich) to make a total of 150 g. 35.4 g of ion-exchanged water was added to a vessel, and 20 g of the above sodium silicate aqueous solution, 25 g of a polymer aqueous solution diluted to a polymer concentration of 1000 ppm, and 19.65 g of 0.1 M HCl were added while stirring, and the mixture was stirred for 2 hours at 30° C. The amount of silica in the aqueous solution before and after the test was measured by the molybdenum yellow method. Polymerizable silica scale inhibition rate (%) = SiO after test 2 (ppm) / SiO before testing 2 Concentration (ppm)×100 The polymerizable silica scale inhibition rate was evaluated according to the following criteria. <Evaluation criteria for polymerizable silica inhibition rate> Suppression rate 55% or more:○ 45~55%:△ 45% or less: × <Example 1> For the polymer (1) obtained in Synthesis Example 1, the above-mentioned polymerizable silica inhibition rate evaluation test was carried out. <Comparative Example 1> For the polymer (2) obtained in Synthesis Example 2, the above-mentioned polymerizable silica inhibition rate evaluation test was carried out. <Comparative Example 2> For the polymer (3) obtained in Synthesis Example 3, the above-mentioned polymerizable silica inhibition rate evaluation test was carried out. <Comparative Example 3> An evaluation test was carried out in the same manner as in the polymerizable silica inhibition rate evaluation test, except that 25 g of ion-exchanged water was added instead of the aqueous polymer solution.
[0030] The experimental results of Example 1 and Comparative Examples 1 to 2 are shown in Table 1.
[0031] [Table 1] In Table 1, "composition" indicates the structural units derived from acrylic acid (salt) / structural units derived from sulfonic acid (salt) groups. The results in Table 1 show that the copolymer of the present disclosure has excellent polymerizable silica scale inhibition ability.
Claims
1. A copolymer comprising a structural unit derived from (meth)acrylic acid (salt) and a structural unit derived from a sulfonic acid (salt) group-containing monomer, The structural unit derived from the sulfonic acid (salt) group-containing monomer is represented by the following general formula (1): A silica scale inhibitor containing a (meth)acrylic acid-based copolymer characterized in that structural units derived from sulfonic acid (salt) group-containing monomers account for 11 mol % or more and 25 mol % or less of structural units derived from sulfonic acid (salt) group-containing monomers relative to 100 mol % of all monomer-derived structures, and that the weight average molecular weight is 9,200 or less (however, excluding copolymers containing, as active ingredients, (1) itaconic acid and (2) maleic acid and / or fumaric acid, in which the blending weight ratio of (1) and (2) is 10-90:90-10 and the sum of (1) and (2) is 80 wt % or more of the monomer composition of the copolymer). 【Chemistry 1】 (In general formula (1), R 1 represents a hydrogen atom or a methyl group, and X and Y each independently represent a hydroxyl group or a sulfonic acid (salt) group (provided that at least one of X and Y represents a sulfonic acid (salt) group. An asterisk represents an atom contained in another structural unit of the same type or different type to which the structural unit represented by general formula (1) is bonded).
2. The silica scale inhibitor according to claim 1, wherein the content of structural units derived from (meth)acrylic acid (salt) in the (meth)acrylic acid-based copolymer is 70 mol % or more and 89 mol % or less, relative to 100 mol % of structural units derived from all monomers constituting the copolymer.
3. The silica scale inhibitor according to claim 1 or 2, wherein the structural unit derived from a sulfonic acid (salt) group-containing monomer is a structural unit derived from 3-allyloxy-2-hydroxypropanesulfonic acid or a salt thereof.
4. A silica scale inhibitor described in any one of claims 1 to 3, wherein the (meth)acrylic acid-based copolymer has a sulfonic acid (salt) group at at least one end of the main chain of the copolymer.
5. A water treatment agent comprising the silica scale inhibitor according to any one of claims 1 to 4.
Citation Information
Patent Citations
Method for controlling scale in process for producing deinked waste paper pulp
JP2002061089A
Scaling inhibitor and method for preventing scaling
JP2003080294A
Water treatment agent and water treatment method
JP2011045861A
Method for preventing silica scale in water system and scale inhibitor, and water treatment method and water treatment agent for preventing silica scale and corrosion of metals
JP2014036912A
Scale inhibitor for geothermal power generation
JP2016064382A